درجة توافر مهارات الإبداع الإداري لدى مديري المدارس الثانوية في دولة الكويت - العجمي، محمد صالح (مركز السنبلة للبحوث والدراسات, 2023)
هدفت الدراسة إلى تعرف درجة توافر مهارات الإبداع الإداري لدى مديري المدارس الثانوية في دولة الكويت من وجهة نظر المديرين ومعلميهم؛ لتحقيق هدف الدراسة تم تطوير استبانة مكونة من (29) فقرة، وتم التأكد من صدقها وثباتها، ومن ثم تم توزيعها على عينة الدراسة المكونة من (300) معلماً ومديراً، وأظهرت نتائج الدراسة أن درجة توافر مهارات الإبداع الإداري من وجهة نظر أفراد عينة الدراسة كان متوسطاً. وأظهرت النتائج عدم وجود فروق ذات دلالة إحصائية في تقديرات أفراد عينة الدارسة لدرجة توافر مهارات الإبداع الإداري تعزى للجنس، والمؤهل العلمي، والخبرة. وأوصت الدراسة في ضوء تلك النتائج بضرورة عمل الدورات التدريبية مستمرة لتنمية مهارات الإبداع الإداري في المؤسسات التربوية. This study aimed at a identifiying the degree of availability of administrative creativity skills among secondary school principals in the State of Kuwait From Principals and Teachers Point of View, and to achieve the goal of the study questionnaire was developed Consisting of (29) paragraph were confirmed validity and reliability, the study sample consisting of (300 Teachers and Principals, the study results showed that the degree of appreciation and the degree of availability of administrative creativity skills from the standpoint of the study sample was a high degree, the lack of significant differences in the study sample to the degree of availability of administrative creativity skills, due to gender and Job title and Experience. In the light of these results, the study recommended the necessity of conducting continuous training courses to develop administrative creativity skills in educational institutions.
Keywords: المهارات الإدارية -- التعليم الثانوي -- مديرو المدارس -- الكويت